Capecitabine maintenance therapy for XT chemotherapy-sensitive patients with metastatic triple-negative breast cancer - Liang, Xu; Di, Lijun; Song, Guohong; Yan, Ying; Wang, Chaoying; Jiang, Hanfang; Li, Huiping (Chinese Journal of Cancer Research, 2014)
Objective: To investigate the efficacy and safety of capecitabine maintenance therapy (MT) after initial capecitabine plus docetaxel (XT) chemotherapy in patients with metastatic triple-negative breast cancer (mTNBC). Methods: Fifty-five mTNBC patients treated with XT chemotherapy between May 2007 and June 2013 were retrospectively analyzed. When initial disease control was achieved by the combination chemotherapy, capecitabine was continued for 32 patients (MT), while 23 patients remained without any treatment (non-MT). We compared progression-free survival (PFS) and safety of both groups. Results: The median PFS of 55 patients was 8.1 months, overall median PFS time of 32 patients in the capecitabine MT group and 23 in the non-MT group was 10.1 vs. 6.7 months (P=0.032), respectively. When compared PFS time of maintenance treatment, single-agent capecitabine prolonged PFS by 7.1 months, for non-MT patients, the PFS without any treatment was 3.1 months, and this between-group difference was statistically significant (P=0.003). Adverse events, including of hematologic toxicity, gastrointestinal toxicities, hand-foot syndrome and abnormal liver function were not significantly different between two groups. Conclusions: After initial disease control was achieved with the XT combination chemotherapy, capecitabine MT can significantly prolong PFS time with a favorable safety profile in mTNBC patients.